Pengaruh Penambahan Ekstrak Tembakau (Nicotiana tabacum) Terhadap Kondisi Histologi Ikan Cupang (Betta splendens) - Haikal Faruqi Saltas; Z. A. Muchlisin; Adrian Damora (Universitas Syiah Kuala, 2021)
The objectives of the study were to determine the effect of tobacco extract dose optimal in anesthesia and see the effect of anesthesia on betta fish (Betta splendens). The fish used in this study is betta fish (Betta splendens) aged 4 months with a size of 2-4 cm with a treatment time of three days. The study was conducted in October 2020. This study used a completely randomized design with seven treatments and three replications. The treatments tested were tobacco extract with doses control, 0,01 ml/L,0,02 ml/L, 0,03 ml/L, 0,04 ml/L, 0,05 ml/L, and 0,1 ml/L. Soaking betta fish is done with a density of one fish for each treatment container. The ANOVA test showed that the difference in the concentration of tobacco extract had no significant effect on survival and blood glucose (P0.05). But it affects the histology of the betta fish's gills and liver. Blood glucose decreased with the addition of tobacco extract 0,01 ml/L to 0,03 ml/L, but increased again beyond the control value at concentrations of 0,04 ml/L to 0,1 ml/L. The color of the betta fish after 3 days of treatment showed an average bright color, and only at the control dose was slightly pale. The condition of betta fish fins after 3 days of treatment was only at a dose of 0,1 ml/L, 0,02 ml/L, 0,03 ml/L, and 0,1 ml/L under normal conditions, but at a control dose, 0,04 ml/L, and 0,05 ml/L the fins were slightly damaged.Keyword : Betta fish, tobacco extract, Survival rate, blood glucose, histology